ETIOTROPIC TREATMENT OF PNEUMONIA IN CHILDREN AT THE CURRENT STAGE - Kholmuradova Zilola Ergashevna (TADQIQOTLAR.UZ, 2025)
Etiotropic treatment of any disease requires, first of all, knowledge of the pathogen and its sensitivity to antibiotics. Since, when meeting with an acute patient, the doctor cannot delay the start of treatment until these issues are clarified, his empirical prescriptions should be carried out taking into account the likelihood of a particular pathogen and its sensitivity. Recent work has shown that the accuracy of the empirical choice of an antimicrobial drug can be very high (80-70%) when taking into account a number of obvious factors [1]. When addressing this issue, one should first of all take into account where the pneumonia developed, since in terms of etiology, community-acquired (“home- acquired”, community-acquired) pneumonia is fundamentally different from hospital- acquired pneumonia. The latter also includes cases of pneumonia developing in a child recently (less than 7 days) discharged from the hospital, as well as in a child receiving antibiotics at home. A special case is pneumonia in people with immunodeficiency, which is distinguished by both its particular severity with “common” pathogens and the participation of opportunistic flora. The Classification of Nonspecific Respiratory Diseases in Children [2] lists the probable causative of pneumonia of these main groups, however, to narrow the range of possible causative agents, it is advisable to supplement these data with two other characteristics - age and the nature of pneumonia.